Analisis Perbandingan Rasio Likuiditas, Rasio Aktivitas, Rasio Solvabilitas Dan Rasio Probabilitas Untuk Menilai Kinerja Perusahaan Manufactur - Marcella Trianita Abur; Rosaria Rudeng; Feby Galih Saputra; Mohammad Ramadhan Priatmojo (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research aims to determine the level of company development so that financial performance can then be assessed. The company's financial performance is the achievement achieved from achieving the company's goals. Likewise, manufacturing companies want to know developments that occur each period. So that in the end the company is able to produce policies that have a positive impact, achieve its goals, and grow good prospects for the company's future. Through financial report analysis, the company's financial performance can be interpreted. This research is qualitative research with a descriptive approach carried out using calculations on qualitative data in the form of financial reports. These financial reports are secondary data obtained from each company's annual report. Meanwhile, the analytical tool used in this research is financial ratio analysis consisting of liquidity ratios, solvency ratios, profitability ratios, activity ratios, using the time series analysis method. In general, the results of this analysis show that the financial condition of each manufacturing company analyzed is quite good. This is proven by the company's ability to deal with various events that have the potential to be detrimental to the company which the company can overcome.